Critical thinking in education - Doğan, Yunus; Güzel, Dilek; Değer, Betül (Nova Science Publishers, Inc., 2024)
Thinking is one of the most fundamental characteristics that distinguish humans from other living beings, and throughout history, the ability to think has been the gateway from the origins of humanity to the present science and technology. The act of thinking is subdivided into various branches such as reflective, creative, analytical, and critical thinking. Individuals capable of critical thinking have been described as courageous, unafraid of taking risks, directing their attention to the process along with the results, synthesizing acquired knowledge, and being judicious. Viewing critical thinking as a skill, coupled with the belief that every skill is teachable, numerous studies and examinations have been conducted on critical thinking in education. It has been stated that individuals who can employ critical thinking in their daily lives are the ones who stand out, make a difference wherever they are, and accomplish successful endeavors. While the speed of accessing information and the diversity of knowledge sources have positive effects, they also have negative implications. Particularly through the internet, various ideas can be integrated into society in mass, and instant direction can be given to society. Hence, the importance of individuals who can utilize critical thinking stages is increasing day by day. Countries recognizing that qualified human resources are an integral part of economic development have incorporated critical thinking skills into their education systems. In our country, within the restructured education system in 2005, critical thinking was included as an interdisciplinary and elective course in the second stage of primary education. Different models have been adopted in embedding critical thinking into educational systems. The content-based approach aims to teach skills while teaching the content of other courses. The skill-based approach argues that critical thinking should be taught as a separate course, teaching its stages. The integrated approach is similar to the content-based approach, advocating for the joint teaching of content and skills. The hybrid approach advocates for the simultaneous use of both content-based and skill-based approaches. Teachers should possess extensive knowledge about methods and strategies that enhance critical thinking and should frequently incorporate these methods and techniques into their lessons. Teachers who motivate students, listen without judgment, and consider individual characteristics contribute to the development of critical thinking skills. While there are factors that enhance elements developing thinking skills, there are also factors that inhibit them. The societal perception of criticism as judgmental or negative has hindered critical thinking. Intelligence level, individual attitudes and perceptions, and environmental factors have significant effects on the development or weakening of critical thinking skills. There are factors that enhance thinking skills and also factors that hinder them. The societal perception regarding criticism has obstructed critical thinking. Intelligence level, individual attitudes and perceptions, and environmental factors significantly impact the development or decay of critical thinking skills. Besides being teachable, critical thinking skills face certain obstacles in their development. Literature suggests that individuals capable of critical thinking tend to have higher intelligence levels. This situation can present itself as either an inherited advantage or disadvantage. Some environmental factors can negatively impact the acquisition of this skill. Teacher qualifications, method and technique knowledge, respect for individual differences, democratic environments, and the resources and time available in classrooms and schools influence the development of critical thinking skills. © 2024 Nova Science Publishers, Inc. All rights reserved.
Keywords: Critical thinking; Critical thinking approaches; Dimensions of critical thinking; Methods in teaching critical thinking